Awareness level on disaster management preparedness in Deuri-Parbaha VDC of Dhanusha , district, Nepal. - Yadav, Ram Dular (2007)
ABSTRACT: The present descriptive cross-sectional study was carried out to assess the current level of awareness regarding disaster management preparedness among people of Deuri-Prabaha VDC Dhanusha District, Nepal over September to December,2007. A total of 306 respondents were randomly chosen and interviewed face-to-face to collect the intended information. The study revealed that female participation was meager (21.2%). among respondents, 55.5% had been presented with low level of knowledge and 65.3% respondents had poor preparedness practice while 88.2% has access to media. Among respondents who had access to media, 50.9% had high level knowledge while 61.8% (who didn't have any access to media) had low level of knowledge. Also 20.9% had received training on disaster management preparedness and 54.7% had good preparedness practice. Among untrained ones, 78.9% had poor preparedness practice. Among, illiterates, 73.6% had poor preparedness practice and among literates, 60.5% had such poor practice. Among respondents having katcha housing , 56.03% had low level of knowledge. Among respondents who have pucca and semi-pucca housing, 62.5% had high level of knowledge. The study also attempted to identify the factors influencing the disaster management preparedness and hierechically the important factors included gender inequality, educational status of respondents, access to media, training regarding preparedness, living condition, lifestyle, ineffective health service, lack of coordination between interrelated agencies, and absence of clear duty and responsibility. On the basis of findings, it is recommended that different effective health education and training activities need to be organized at community level and people need to be oriented with preparedness guidelines.